Interfollicular Hodgkin’s lymphoma: A diagnostic challenge for pathologists - Maneesh K. Vijay; Neha Sethi (Indian Journal of Pathology and Microbiology)
Interfollicular Hodgkin’s lymphoma (IFHL) is a rare pattern of classical Hodgkin’s lymphoma (CHL) showing reactive follicular hyperplasia with involvement of the interfollicular area by HL. Two cases are reported in this study having primary IFHL out of total of 500 cases of CHL reported at our center. Diagnosis of IFHL was made on the basis of morphological and immunohistochemical features. As they represent an early stage of the disease, their identification and awareness s very important to get proper treatment at its earliest. This variant is very unusual and is diagnostically challenging for pathologists.